Specificity of Linear Motifs That Bind to a Common Mitogen-Activated Protein Kinase Docking Groove - Garai, Ágnes (2012)
Mitogen activated protein kinases (MAPKs) have a docking groove that interacts with linear motifs in binding partners. To determine the structural basis of binding specificity between MAPKs and docking motifs, we quantitatively analyzed the ability of fifteen linear motifs from diverse MAPK partners to bind to c-Jun N-terminal kinase 1 (JNK1), p38α and extracellular signal-regulated kinase 2 (ERK2). Classical docking motifs mediated highly specific binding only to JNK1, and only motifs with a sequence pattern distinct from the classical MAPK binding docking motif consensus could differentiate between the topographically similar docking grooves of ERK and p38. We also solved the crystal structures for four MAPK-docking peptide complexes that represented JNK-specific, ERK-specific or ERK- and p38-selective binding modes. These structures revealed that the regions located in between consensus positions in the docking motifs showed conformational diversity. Although the consensus positions in the docking motifs served as anchor points that bound to common MAPK surface features and mostly contributed to docking in a non-discriminatory fashion, specificity was determined mainly by the conformation of the intervening region between the anchor points. These insights enabled us to successfully design peptides with tailored MAPK binding profiles by rationally changing the length and amino acid composition of docking motif regions located between anchor points. We present a coherent structural model underlying MAPK docking specificity that reveals how short linear motifs binding to a common kinase docking groove can mediate diverse interaction patterns and contribute to correct MAPK partner selection in signaling networks.